2014
DOI: 10.3758/s13414-014-0631-5
|View full text |Cite
|
Sign up to set email alerts
|

The automatic and the expected self: separating self- and familiarity biases effects by manipulating stimulus probability

Abstract: Attentional control over prepotent responses has previously been shown by manipulating the probability with which stimuli appear. Here, we examined whether prepotent responses to self-associated stimuli can be modulated by their frequency of occurrence. Participants were instructed to associate geometric shapes with the self, their mother, or a stranger before having to judge whether the sequential shape-label pairs matched or mismatched the instruction. The probability of the different shape-label pairs was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(147 citation statements)
references
References 21 publications
14
130
0
3
Order By: Relevance
“…This does not nec essarily mean that the top-down settings from the label are based on conscious expectancies. In a recent article (Sui, Sun, Peng, & Humphreys, 2014) we showed that the self advantage remains in self-label matching even when participants have no expectancies for self-related stimuli, whereas biases for other people (e.g., for friend-related stimuli over stimuli linked to a stranger) disappear. Nevertheless, there is good'reason to think that the presence of the label does play a role in driving self bias effects with single stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…This does not nec essarily mean that the top-down settings from the label are based on conscious expectancies. In a recent article (Sui, Sun, Peng, & Humphreys, 2014) we showed that the self advantage remains in self-label matching even when participants have no expectancies for self-related stimuli, whereas biases for other people (e.g., for friend-related stimuli over stimuli linked to a stranger) disappear. Nevertheless, there is good'reason to think that the presence of the label does play a role in driving self bias effects with single stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to this, Sui et al (2014) found that increasing the probability of the different pairings facilitated responses to all stimuli, compared with when the pairings had A c c e p t e d M a n u s c r i p t…”
mentioning
confidence: 88%
“…Based on previous studies showing that participants can rapidly gain associations between the shapes and labels just after an association instruction (Sui et al, 2012(Sui et al, , 2014, we had participants perform 24 practice trials to reinforce associations between the letters and shapes trials where they indicated their responses ('match' or 'mismatch') by pressing buttons on a keyboard. After each trial they were provided with feedback on accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Information encoded in relation to the self tends to be better remembered and recollected than other information (Turk, Cunningham, & Macrae, 2008); people respond faster to their own faces rather than to those of others (Ma & Han, 2010;Theeuwes, Van der Stigchel, & Olivers, 2006); responses to their own objects are faster and more accurate compared to responses to objects owned by others (Turk, van Bussel, Waiter, & Macrae, 2011). Recently, the effects of self-biases have been found even in simple perceptual tasks (Sui, He, & Humphreys, 2012;Sui, Sun, Peng, & Humphreys, 2014). Specifically, in a task where participants associate simple geometric shapes with personal labels (you, friend, or stranger) and then immediately judge whether subsequent label-shape pairings matched, there are faster responses and higher perceptual sensitivity to self-associations compared with otherassociations (Sui et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation